PERAN STORE ATMOSPHERE, SHOPPING LIFESTYLE, DAN PRICE PADA IMPULSE BUYING DENGAN POSITIVE EMOTION SEBAGAI VARIABEL INTERVENING : PERAN STORE ATMOSPHERE, SHOPPING LIFESTYLE, DAN PRICE PADA IMPULSE BUYING DENGAN POSITIVE EMOTION SEBAGAI VARIABEL INTERVENING - Asna Ulya Rosidah; Vania , Amelindha (Universitas Islam Lamongan, 2023)
This research is motivated by the impulsive buying behavior carried out by consumers when shopping. The aim of this research is to explain the influence of store atmosphere, shopping lifestyle, and price on impulse buying, which is mediated by positive emotions. The method used in this research is a quantitative method. Sampling used the purposive sampling technique. Data analysis in this research was carried out using PLS. The research results show that there is a significant indirect influence between store atmosphere, shopping lifestyle, and price on impulse buying through positive emotion in Ninety-Fashion Hijab in Blitar City. This proves that the hypothesis in this research cannot be fully accepted.